Ensino de língua portuguesa por meio da análise de design e de elementos discursivos em fake news políticas: proposta de cartilha para identificação de notícias falsas - Nascimento, Isadora Oliveira do (2020)
The Post-Truth Era is considered to be a period when objective facts have less power to shape public opinion than personal opinions (OXFORD LANGUAGES, c2020). As a by-product of the post-truth, fake news appears, which, in turn, is strengthened by the phenomena of filtered bubbles, created from the action of algorithms that aim to capture the preferences of users. Considering this context, this research aims to propose procedures for checking information that circulates on digital platform sites for high school students, through a booklet, considering different designs of political fake news and their discretization in discursive components. Thus, an assumption of work that we want to investigate is that fake news is endowed with verbimagetic and discursive elements that can allow their identification, even if posted on different digital platforms and that such systematization is not carried out in schools. The theoretical basis to which we allied comes from New London Group (1996), Cope and Kalantzis (2000; 2015) for the conceptions of Multiliteracy; about criticality, we employ Janks (2016); about Information Disorder, we are guided by Wardle (2017; 2018); for Fake News, we used Tobias (2018), Seserig and Máximo (2017); Monteiro et. al ([2018]). For the notions of bubbles, we rely on Pariser (2012). On Post-truth, we are guided by the studies of Santaella (2018), Oxford Languages (c2020), Coelho (2018), and D’ancona (2018). In compliance with the objectives set, qualitative research of a descriptive nature was carried out, in which we built a corpus of six rumors generated around Adélio Bispo after the 2018 elections, on the digital platforms Facebook, Youtube, Twitter, and WhatsApp, already demystified in check sites. After the analysis, we were able to capture the categories present in this type of corpus and, subsequently, classify them in terms of expression and content. The results show that, despite the social network in which they are published, fake news has a pattern of elements that allow their identification, some of which are perceptible through the design elements that compose it (expression elements) and others, through the analysis of textual / imagery composition through more in-depth checking (content elements), which were organized in an information booklet for teachers and high school students